Pengembangan Aplikasi Android OMV Sebagai Media Pembelajaran Pada Materi Penggunaan Teknologi Perkantoran Kelas X OTKP 3 di SMK Ketintang Surabaya - Sevina Dinul Islamiyah; Durinta Puapasari (Universitas Negeri Surabaya, 2021)
Education is important for preparing children to face their lives in the future. Teacher learning in schools in the delivery of material requires learning media in accordance with the development of students. In the digital era like now digital usage is more popular so learning by utilizing electronic media is more appropriate. This research aims to describe the process of developing Office Machine Virtual (OMV) applications as a 3D-based learning media on the Use of Office Technology material X OTKP 3 class subjects at SMK Ketintang Surabaya. This type of research is Research and Development. This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The development research process carried out has gone through stages in accordance with the ADDIE development model, namely the analysis, design, development, implementation, and evaluation stages. However, the stages of development, implementation, and evaluation were not carried out due to the limitations of the researchers. This research resulted in an android application that contains two menus namely the material menu and evaluation. The material menu is equipped with 3D images that can be rotated according to the wishes of students. The evaluation menu consists of three levels of question stages and a practical tutorial.